Development of field-applicable endogenous internally controlled recombinase-aided amplification (EIC-RAA) assays for the detection of human papillomavirus genotypes 6 and 11 using sample releasing agent. Issue 11 (November 2022) - He, Anna; Fang, Cheng; Ming, Yue; Tan, He; Zhang, Mengyi; Zhang, Ruiqing; Li, Jingyi; Nie, Mingzhu; Li, Fengyu; Hu, Yaxin; Shen, Xinxin; Rong, Xiuge; et al.
Abstract: Objective: Human papillomavirus (HPV) 6 and 11 are the two most common low-risk HPV subtypes, accounting for more than 90% of condyloma acuminatum. A simple, accurate and rapid screening method to be applied in community-level hospitals is in high demand. Methods: Endogenous internally controlled recombinase-assisted amplification (EIC-RAA) assays for HPV6 and 11 were performed in a single closed-tube at 39 °C within 30 min. The sensitivity and specificity of EIC-RAA were examined using recombinant plasmids and pre-tested HPV DNA. A total of 233 clinical samples were collected, and the DNA was extracted by traditional multi-step extraction, or sample releasing agent, before analysis by EIC-RAA. For comparison, HPV detection via Quantitative real-time PCR (qPCR) was also performed. Results: The sensitivity of EIC-RAA analysis was 10 copies/reaction for HPV6, 100 copies/reaction for HPV11, and 100 copies/reaction for the human β-globin gene. No cross-reaction was observed with other HPV subtypes. Clinical performance of the EIC-RAA assay achieved a 100% of concordance rate with the commercial HPV qPCR kit. Further, the EIC-RAA assay achieved a 100% of concordance rate when using multi-step extracted DNA and sample releasing agent-processed DNA. Summary: The EIC-RAA assay for HPV6 and 11 detection possesses the advantages of accuracy, simplicity and rapidity, and demonstrates great potential to be used in community-level hospitals for field investigation. Highlights: The EIC-RAA assays for HPV6 and 11 possess high sensitivity and specificity. The endogenous human β-globin can effectively eliminate false-negatives or invalid amplification results, increasing the reliability of the EIC-RAA assay. The EIC-RAA assays for the detection of HPV 6 and 11 using sample releasing agent show the advantages of fast detection speed and simple operation. Abstract : Human papillomavirus 6 and 11; Human β-globin gene; Endogenous internally controlled recombinase-assisted amplification; Sample releasing agent.